2003
DOI: 10.1038/nm979
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of pluripotency in human and mouse embryonic stem cells through activation of Wnt signaling by a pharmacological GSK-3-specific inhibitor

Abstract: Human and mouse embryonic stem cells (HESCs and MESCs, respectively) self-renew indefinitely while maintaining the ability to generate all three germ-layer derivatives. Despite the importance of ESCs in developmental biology and their potential impact on tissue replacement therapy, the molecular mechanism underlying ESC self-renewal is poorly understood. Here we show that activation of the canonical Wnt pathway is sufficient to maintain self-renewal of both HESCs and MESCs. Although Stat-3 signaling is involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

69
1,665
17
24

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,895 publications
(1,775 citation statements)
references
References 46 publications
69
1,665
17
24
Order By: Relevance
“…Additionally, b-catenin activity is capable of maintaining an undifferentiated state in teratomas, implying that b-catenin signaling may push germ cells towards a proliferative undifferentiated state (Kielman et al, 2002). This finding agrees with the work of many studies that uncovered a role for b-catenin in stem cell maintenance (Li et al, 2003;Willert et al, 2003;Liu et al, 2004;Sato et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Additionally, b-catenin activity is capable of maintaining an undifferentiated state in teratomas, implying that b-catenin signaling may push germ cells towards a proliferative undifferentiated state (Kielman et al, 2002). This finding agrees with the work of many studies that uncovered a role for b-catenin in stem cell maintenance (Li et al, 2003;Willert et al, 2003;Liu et al, 2004;Sato et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…In the hematopoietic system, Wnt/ b-catenin signaling maintains cells in a pluripotent proliferative state (Willert et al, 2003). Similar findings were found in human embryonic stem cells where inhibition of GSK3b and subsequent b-catenin stabilization maintained the pluripotency of the cells in culture (Sato et al, 2004). During Wnt-induced transformation of mammary tissue this link to stem cell renewal is thought to result in preferential accumulation and induction of cancer from mammary progenitor cells (Li et al, 2003).…”
supporting
confidence: 52%
“…GSK-3b inhibition through BIO is of particular clinical interest, as the effects can preserve and support proliferation of normal hematopoietic stem cells through canonical WNT signaling (Sato et al, 2004). In contrast, GSK-3b inhibition by BIO suppressed proliferation of various leukemia cell lines, including K562 (Holmes et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…6A, 6B). However, previous reports have also shown that b-catenin/Wnt signaling in undifferentiated ESCs can maintain pluripotency [37,41,42], implying that GSK-3 inhibition alone would interfere with neurogenesis. To overcome this problem, we decided to stimulate neural specification by additionally adding EGF and bFGF [20,43,44].…”
Section: The Crb2-kd Phenotype Can Be Rescued By Gsk3b Inhibition Andmentioning
confidence: 95%